Cellular plasticity in musculoskeletal development, regeneration, and disease - Kaji, Deepak A. (J Orthop Res, 2019)
In this review, we highlight themes from a recent workshop focused on “Plasticity of Cell Fate in Musculoskeletal Tissues” held at the Orthopaedic Research Society’s 2019 annual meeting. Experts in the field provided examples of mesenchymal cell plasticity during normal musculoskeletal development, regeneration, and disease. A thorough understanding of the biology underpinning mesenchymal cell plasticity may offer a roadmap for promoting regeneration while attenuating pathologic differentiation.